KONTRIBUSI PAJAK KENDARAAN BERMOTOR PADA UNIT - Muhammad Alfian Rosyadi; Pusvita Indria Mei Susilowati (Universitas Lambung Mangkurat, 2021)
This research..aims to find out..and..analyze the level of contribution of motor vehicle tax revenue (PKB) to the regional revenue service unit (UPPD) Banjarmasin I. The type of data used is quantitative data, such as target and realization data. motor vehicle tax (PKB) from 2019-2020. The results obtained are the contribution of motor vehicle tax (PKB) to the regional revenue service unit (UPPD) Banjarmasin I is classified as effective and has increased.